2021
DOI: 10.1016/j.redox.2021.101969
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic mutation in Fsip1 impairs acrosome vesicle formation and attenuates flagellogenesis in mice

Abstract: Fibrous sheath interacting protein 1 (Fsip1) is a cytoskeletal structural protein of the sperm flagellar proteome. A few studies have reported that it plays a vital role in the tumorigenesis and cancer progression. However, little is known about the role of Fsip1 in spermatogenesis and mammalian sperm flagellogenesis. Fsip1 protein showed the highest expression in round spermatids, and was translocated from nucleus to the anterior region of the elongating spermatid head. To investigate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Examples of peaks with a dose-respond trend across the three tertiles were FSIP1 gaining in H3K4me3 (important for acrosomal reaction and sperm flagellation; Fig. 3H) (Gamallat et al, 2021), and BRD1 losing in H3K4me3 chromatin interacting protein involved in brain development; Fig. 3I) (Severinsen et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of peaks with a dose-respond trend across the three tertiles were FSIP1 gaining in H3K4me3 (important for acrosomal reaction and sperm flagellation; Fig. 3H) (Gamallat et al, 2021), and BRD1 losing in H3K4me3 chromatin interacting protein involved in brain development; Fig. 3I) (Severinsen et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Protein-protein interaction network analysis by STRING showed that FSIP2 may be highly connected with FSIP1 and CFAP69. The protein level of IFT20 was downregulated significantly in the Fsip1 -/-mice testis and FSIP1 interacted with IFT20 involving sperm flagellum assembly [42]. Additionally, SPEF2 possible had the role in protein through the manchette towards the sperm tail interacting with IFT20 and CFAP69 [55,56].…”
Section: Discussionmentioning
confidence: 96%
“…However, no variations had been reported to cause the lengthened MS sperm in human, the similar phenotype as in FSIP2.Different from AKAP4, AKAP3, and FSIP1, FSIP2 was transcribed in late spermatocyte development [30]. Deficiencies of FSIP2 were associated with DFS, MMAF and globozoospermia [31][32][33]42]. Recurrent FSIP2 amplification had been linked to testicular germ cell tumor [63], and FSIP2 was also reported as a novel potential candidate gene for nonobstructive azoospermia [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FSIP1 is a fibrous sheath-interacting protein, and knockout of Fsip1 provoked abnormal sperm head and flagellum ultrastructure, and impaired acrosome vesicle formation and flagella genesis in mice 40. Moreover, several other genes were initially reported to be relevant to MMAF, and the deleterious mutations in these genes were later found in patients with globozoospermia.…”
Section: Discussionmentioning
confidence: 99%